Demulsification of Remaining Waste (Water In Oil Emulsions) After Removal Of Phenol In Emulsion Liquid Membrane Process (Journal of Engineering, 2016)
The aim of present work is to study the removal of phenol present in aqueous feed solution by the emulsion liquid membrane technique using kerosene as a diluent, sodium hydroxide as a stripping agent, and sorbitan monooleate (Span 80) as a surfactant. The parameters studied were: surfactant concentration, volume ratio of membrane phase to internal phase, and stirring speed. It was found that more than 98% of phenol can be removed at the conditions were surfactant concentration 2% (v/v), volume ratio of membrane phase to internal phase 5:1 and stirring speed 400 rpm. Maximum phenol extraction efficiency at 7 minutes of process time was observed. It was found that there was a good agreement between the standard kerosene and the upper layer that resulted after the demulsification of the remaining waste by applying centrifuge. Thus, it is possible to reuse this layer to prepare a new emulsion of the membrane phase.